2018
DOI: 10.1007/s13744-018-0595-6
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Anopheles spp. (Diptera: Culicidae) in an Amazonian Urban Area

Abstract: The genus Anopheles encompasses several species considered as vectors of human infecting Plasmodium. Environmental changes are responsible for behavior changes in these vectors and therefore the pattern of malaria transmission. To better understand the dynamics of malaria transmission, this study aimed at identify the species of adult anophelines found in a malaria endemic urban area of the Amazon region, Mâncio Lima, located in the Acre State Brazil. Using Shannon-type light traps installed at 11 collection p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…albitarsis s.l. is also frequently found in natural and man-made larval habitats widely distributed across the town, especially in fish-farming ponds [19, 20].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…albitarsis s.l. is also frequently found in natural and man-made larval habitats widely distributed across the town, especially in fish-farming ponds [19, 20].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…A great variety of potential vectors have been recorded in the deforested areas of the Amazon [ 30 32 ], but the frequent occurrence of morphologically indistinguishable sibling species, which form species complexes [ 33 ], means that vectors are often misidentified or cryptic species boundaries go undetected [ 34 36 ]. Some vectors, such as Nyssorhynchus triannulatus and Anopheles peryassui , inhabit the forest edge, away from domestic environments and conventional vector control activities, but may be associated with human activity such as deforestation [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…)darlingi is considered one of the most effective primary vectors due to its high anthropophilic behavior, high abundance in certain areas, susceptibility to infection by several Plasmodium species and plastic behavior [21]. This species can also adapt to diverse habitats, including habitats developed because of human activities [44,24]. Our study showed that both mosquito species (An.…”
Section: Biting Activitymentioning
confidence: 63%
“…In addition, this species is susceptible to infection by several Plasmodium species and displays exo/endophagic depending on host availability and environmental characteristics [21]. It can adapt to several types of habitat, including anthropic activity-related hatcheries [22][23][24]. Social, environmental, economic, demographic and climatic changes can signi cantly in uence the distribution of anophelines in endemic areas [25][26][27].…”
Section: Introductionmentioning
confidence: 99%